2012
DOI: 10.1371/journal.pone.0052498
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction and Evaluation of the Synthetic Bacterial MEP Pathway in Saccharomyces cerevisiae

Abstract: Isoprenoids, which are a large group of natural and chemical compounds with a variety of applications as e.g. fragrances, pharmaceuticals and potential biofuels, are produced via two different metabolic pathways, the mevalonate (MVA) pathway and the 2-C-methyl-D-erythritol 4-phosphate (MEP) pathway. Here, we attempted to replace the endogenous MVA pathway in Saccharomyces cerevisiae by a synthetic bacterial MEP pathway integrated into the genome to benefit from its superior properties in terms of energy consum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(39 citation statements)
references
References 73 publications
(112 reference statements)
2
37
0
Order By: Relevance
“…Given the variety and essentiality of isoprenoid products in P. falciparum, it is likely that isoprenoid synthesis by the MEP pathway is regulated to control the product availability of IPP and DMAPP. Two ATPs and 3 NADPHs are consumed for the production of each IPP molecule from glucose (142). The cell likely regulates this pathway to optimize energy consumption.…”
Section: Regulation Of Isoprenoid Synthesismentioning
confidence: 99%
“…Given the variety and essentiality of isoprenoid products in P. falciparum, it is likely that isoprenoid synthesis by the MEP pathway is regulated to control the product availability of IPP and DMAPP. Two ATPs and 3 NADPHs are consumed for the production of each IPP molecule from glucose (142). The cell likely regulates this pathway to optimize energy consumption.…”
Section: Regulation Of Isoprenoid Synthesismentioning
confidence: 99%
“…Screening for DXP pathway functionality via resistance to the HMGR inhibitor lovastatin was deemed to be unreliable and subject to false positives, likely due to acquired resistance, as reported previously (Partow et al, 2012). To provide a definitive metric for DXP functionality, deletion of one of the first three steps in the mevalonate pathway in S. cerevisiae was considered the best approach since it enables screening for mevalonate-independent growth.…”
Section: Resultsmentioning
confidence: 93%
“…In the first report, seven genes from E. coli encoding the core DXP pathway enzymes were expressed in S. cerevisiae and the pathway was deemed to be functional based on growth of this strain in the presence of lovastatin, an inhibitor of the mevalonate pathway enzyme 3-hydroxy-3-methyl-glutaryl-CoA (HMG-CoA) reductase (Maury et al, 2008). However, a follow-up study by the same group demonstrated that insensitivity to lovastatin was insufficient evidence for DXP pathway functionality since it was not possible to complement a knockout of the mevalonate pathway gene ERG13 , encoding HMG-CoA synthase (Partow et al, 2012). Soon afterwards, an independent study confirmed that expression of the E. coli DXP pathway genes was insufficient to complement an ERG13 knockout in S. cerevisiae (Carlsen et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overexpression of key regulatory enzymes of the native DXP pathway has been also utilized to enhance IPP and DMAPP production in prokaryotes (13,(34)(35)(36)(37). Similarly, in the eukaryotic system, efforts have been made to enhance isoprenoid production via (i) bypassing the endogenous regulation of the MVA pathway in Saccharomyces cerevisiae (38,39) or (ii) modulating the expression of endogenous/homologous enzymes for higher production of isoprenoid-based biofuels in yeast (11,(40)(41)(42). The metabolic engineering efforts for either endogenous or heterologous gene expression have increased the production of a vast array of isoprenoid-based biofuels or fuel precursors.…”
Section: Introductionmentioning
confidence: 99%